2020
DOI: 10.1101/2020.08.11.246306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Purinergic signaling controls spontaneous activity in the auditory system throughout early development

Abstract: Spontaneous bursts of electrical activity in the developing auditory system arise within the cochlea prior to hearing onset and propagate through future sound processing circuits of the brain to promote maturation of auditory neurons. Studies in isolated cochleae revealed that this intrinsically generated activity is initiated by ATP release from inner supporting cells (ISCs), resulting in activation of purinergic autoreceptors, K+ efflux and subsequent depolarization of inner hair cells (IHCs). However, littl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…Apart from the activity mediated by supporting cells, IHCs have the intrinsic capacity to fire action potentials with different patterns along the baso-apical axis (Eckrich et al, 2018;Harrus et al, 2018;Johnson et al, 2011;Kros et al, 1998; but see Sendin et al, 2014). In turn, the electrical activity from IHCs excites primary sensory neurons (spiral ganglion neurons) that by P0 fire characteristic intermittent bursts of action potentials (Babola et al, 2020;Coate et al, 2019;Glowatzki and Fuchs, 2002;Zhang-Hooks et al, 2016).…”
Section: From the Cochleamentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the activity mediated by supporting cells, IHCs have the intrinsic capacity to fire action potentials with different patterns along the baso-apical axis (Eckrich et al, 2018;Harrus et al, 2018;Johnson et al, 2011;Kros et al, 1998; but see Sendin et al, 2014). In turn, the electrical activity from IHCs excites primary sensory neurons (spiral ganglion neurons) that by P0 fire characteristic intermittent bursts of action potentials (Babola et al, 2020;Coate et al, 2019;Glowatzki and Fuchs, 2002;Zhang-Hooks et al, 2016).…”
Section: From the Cochleamentioning
confidence: 99%
“…The spatial activity in the inferior colliculus and auditory cortex in rodents has recently been studied by combining mesoscale calcium imaging with high spatial resolution two-photon microscopy. In the inferior colliculus, there are discrete, bilateral stationary bands of spontaneous activity oriented within prospective isofrequency domains (Babola et al, 2020). Bilateral bands are present as early as P1, and their frequency increases until P11-P12.…”
Section: From the Cochleamentioning
confidence: 99%
“…ATP activates autoreceptors on the inner supporting cells (Babola et al., 2020; Tritsch & Bergles, 2010; Tritsch et al., 2007; Wang et al., 2015). Pharmacological inhibition or genetic deletion of purinergic receptors revealed that the supporting cell firing relies on the metabotropic purinergic receptors P2RY1 at least from birth to hearing onset (Babola, Li, et al., 2021). The activation of P2RY1 receptors of the inner supporting cells induces the release of K + from these cells.…”
Section: Spatial Organization Of the Neuronal Spontaneous Activity According To The Modality In Early Developmental Stagesmentioning
confidence: 99%
“…In the mammalian auditory system, extracellular ATP and P2 purinergic signaling is required for spontaneous activity in supporting cells (Babola et al, 2020;Babola et al, 2021). Previous work has shown that pharmacological block of P2RY1 receptors and downstream phospholipase C-β (PLC-β) signaling components blocked spontaneous activity in supporting cells (Babola et al, 2020).…”
Section: P2yr1-er Signaling Underlies Spontaneous Calcium Activity In Supporting Cells But Not In Hair Cellsmentioning
confidence: 99%
“…For coordinated waves of activity among hair cells, concurrent waves of calcium propagate through glia-like supporting cells that surround or are adjacent to hair cells. In cochlear supporting cells, this activity is dependent on ATP and purinergic signaling and propagates via gap junction channels between supporting cells (Tritsch et al, 2007;Ceriani et al, 2019;Babola et al, 2021). Ultimately, ATP signaling in supporting cells drives spontaneous activity in nearby auditory hair cells.…”
Section: Introductionmentioning
confidence: 99%